Effects of water temperature on development and heavy metal toxicity change in two midge species of Chironomus riparius and C. yoshimatsui in an era of rapid climate change - Mo, Hyoung-ho; Yoo, DongHun; Bae, Yeon Jae; Cho, Kijong (Entomological research, 2013)
Climate change is the most significant stressor that is anticipated increasingly to affect human and global ecosystems. Arthropods, including insects, are particularly vulnerable to global warming and this group is often used for various ecotoxicological tests. In addition, temperature is one of the most important toxicity-modifying factors in ecotoxicology. Therefore, temperature dependent toxicological research is required to obtain ecologically relevant conclusions during the current era of rapid climate change. This study shows that two midge species (Chironomus ripariusMeigen and C. yoshimatsuiMartin etSublette) exhibit different developmental characteristics and responses to cadmium and lead heavy metals with temperature. The former species is an internationally standardized test species in ecotoxicological studies, whereas the latter species is native to Korea. Hence, even though these two species belong to the same genus, Chironomus, their development differs with temperature, which leads to different responses to heavy metals. There was a decline in developmental time (from egg and larva to pupa) for both species with temperature; however, there was a species difference in the rate of decline. In the acute toxicity test, the 48-hr LC50 values for cadmium and lead decreased with temperature for both species. In the chronic toxicity test, emergence rates tended to decrease with temperature, except for when C. yoshimatsui was exposed to cadmium.